Nephroprotective Effect of the Virgin Olive Oil Polyphenol Hydroxytyrosol in Type 1-like Experimental Diabetes Mellitus: Relationships with Its Antioxidant Effect - María Dolores Rodríguez-Pérez (MDPI AG, 2021)
The aim of this study was to determine whether hydroxytyrosol administration prevented kidney damage in an experimental model of type 1 diabetes mellitus in rats. Hydroxytyrosol was administered to streptozotocin-diabetic rats: 1 and 5 mg/kg/day p.o. for two months. After hydroxytyrosol administration, proteinuria was significantly reduced (67–73%), calculated creatinine clearance was significantly increased (26–38%), and the glomerular volume and glomerulosclerosis index were decreased (20–30%). Hydroxytyrosol reduced oxidative and nitrosative stress variables and thromboxane metabolite production. Statistical correlations were found between biochemical and kidney function variables. Oral administration of 1 and 5 mg/kg/day of hydroxytyrosol produced an antioxidant and nephroprotective effect in an experimental model of type 1-like diabetes mellitus. The nephroprotective effect was significantly associated with the systemic and renal antioxidant action of hydroxytyrosol, which also influenced eicosanoid production.